DASAR PENILAIAN BUMI DAN BANGUNAN DIBAWAH HARGA PASAR (STUDI DI DIPENDA KABUPATEN MOJOKERTO) - David Widianto (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
Abstract One problem in determining Sales Value of Tax Object (NJOP) for Land Value Tax (PBB) Office for Regional Revenue (Dipenda) of Mojokerto Regency is considered as below the market price of building and land tax valuation. NJOP of PBB is very closely related to the process of land and building valuation as one object of PBB. Therefore, the valuation of land and building is one initial from determination of value/ price per meter of land and building in NJOP of PBB. The aim of this journal are to know what is based and government factors of local government Mojokerto district to do assessment of land value tax below the market price. This journal based on empiric juridical method. The result of study in the field showed that Office for Regional Revenue (Dipenda) of Mojokerto Regency makes the valuation of land considered as mass valuation is based on selling price comparison of average indication value (NIR) for land included in individual valuation category by valuing directly in the field. Whereas, the valuation of building is based on system of computer application. The building valuation considered as mass valuation category is mady by using SPOP application while for individual valuation is made by using DBKB 2000. The valuation result of below the market price land and building is influenced by some substantial (regulation), structural (Dipenda Apparatus), social, economic, and political factors. Key words: basic, land and building valuation,below market price Abstrak Diantara permasalahan penetapan Nilai Jual Objek Pajak (NJOP) untuk Pajak Bumi dan Bangunan (PBB) di Dinas Pendapatan Daerah (Dipenda) Kabupaten Mojokerto adalah penilaian bumi dan bangunan di bawah harga pasar. NJOP PBB sangat berkaitan dengan proses penilaian bumi dan bangunan sebagai objek dari PBB. Sehingga pelaksanaan penilaian bumi dan bangunan adalah embrio dari ditetapkannyaÂ  nilai/ harga per meter terhadap bumi dan bangunan di NJOP PBB. Tujuan jurnal ini untuk mengetahui apa dasar dan faktor pemerintah daerah kabupaten Mojokerto melakuksan penilaian bumi dan bangunan dibawah harga pasar. Metode penulisan jurnal ini adalah yuridis empiris. Hasil dari penelitian dilapangan, bahwa dasar Dipenda Kabupaten Mojokerto melakukan penilaian bumi dalam kategori penilaian masal menggunakan perbandingan harga jual dari Nilai Indikasi Rata- Rata (NIR), untuk bumi yang termasuk dalam kategori penilaian individu dengan menilai langsung kelapangan. Sedangkan dasar penilaian bangunan menggunakan sistem aplikasi komputer, untuk penilaian bangunan dalam kategori penilaian masal dengan aplikasi SPOP sedangkan Untuk kategori penilaian individu dengan aplikasi DBKB 2000. Hasil penilaian bumi dan bangunan dibawah harga pasar dipengaruhi oleh faktor subtansi (Peraturan) , struktur (aparat Dipenda), sosial, ekonomi dan politik. Â  Kata kunci: dasar, penilaian bumi dan bangunan, dibawah harga pasar